2019
DOI: 10.1016/j.jpowsour.2019.05.062
|View full text |Cite
|
Sign up to set email alerts
|

Durability and degradation of vapor-fed direct dimethyl ether high temperature polymer electrolyte membrane fuel cells

Abstract: Dimethyl ether (DME) combines high energy density with easy handling and low toxicity and is therefore an attractive fuel. The absence of carbon-carbon bonds allows for electro-oxidation with good kinetics and it is therefore particularly interesting for use in fuel cells. This work presents the first durability studies of vapor-fed direct dimethyl ether fuel cells with phosphoric acid doped polybenzimidazole membranes as electrolytes. Fuel cells are operated in direct DME mode at 160 and 200 °C and the cell v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 60 publications
1
1
0
Order By: Relevance
“…More specifically the formed NH 4 + ions react with the PO 4 3− groups, consequently resulting in a loss of conductivity. Similar to the results reported here, Vassiliev et al [ 68 ] reports on the possible chemical incompatibility between the other organic fuels and the electrolyte in HT membranes doped with PA. More specifically, it was concluded that the probable reasons were that the catalyst deactivation and/or acid depletion within the electrode occurred.…”
Section: Resultssupporting
confidence: 91%
“…More specifically the formed NH 4 + ions react with the PO 4 3− groups, consequently resulting in a loss of conductivity. Similar to the results reported here, Vassiliev et al [ 68 ] reports on the possible chemical incompatibility between the other organic fuels and the electrolyte in HT membranes doped with PA. More specifically, it was concluded that the probable reasons were that the catalyst deactivation and/or acid depletion within the electrode occurred.…”
Section: Resultssupporting
confidence: 91%
“…59 Another mode of PA loss for cells operated with a direct feed of organic fuels, such as methanol or dimethyl ether, is the chemical formation of organic phosphate derivatives within the membrane. 68,69 These alkyl phosphates are less conducting and more volatile than the pure PA, and may be responsible for the relatively fast performance degradation of direct methanol and direct dimethyl ether HT-PEMFCs. 70 However, the relatively low methanol slip from the reformer for HT-PEMFCs has been found to have a very limited effect on the performance durability.…”
Section: Acid Lossmentioning
confidence: 99%